Nuclear transfer reaction measurements at the ESR—for the investigation of the astrophysical 15O(α, γ)19Ne reaction. (26th November 2015) - Doherty, D T; Woods, P J; Litvinov, Yu A; Najafi, M Ali; Bagchi, S; Bishop, S; Bo, M; Brandau, C; Davinson, T; Dillmann, I; Estrade, A; Egelhof, P; et al.
Abstract: Astrophysical x-ray bursts are thought to be a result of thermonuclear explosions on the atmosphere of an accreting neutron star. Between these bursts, energy is thought to be generated by the hot CNO cycles. The 15 O( α, γ ) 19 Ne reaction is one reaction that allows breakout from these CNO cycles and into the rp-process to fuel outbursts. The reaction is expected to be dominated by a single 3/2 + resonance at 4.033 MeV in 19 Ne, however, limited information is available on this key state. This work reports on a pioneering study of the 20 Ne( p, d ) 19 Ne reaction, performed in inverse kinematics at the experimental storage ring (ESR) as a means of accessing the astrophysically important 4.033 MeV state in 19 Ne. The unique, background free, high luminosity conditions of the storage ring were utilized for this, the first transfer reaction performed at the ESR. The results of this pioneering test experiment are presented along with suggestions for future measurements at storage ring facilities.